Implementasi E-Commerce Dengan Teknik SEO dan Strategi Pemasaran 4P Untuk Meningkatkan Penjualan Produk Aksesoris Motor Pada XYZ Motoshop - Dedi Riandika; Agus Umar Hamdani (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
XYZ Motoshop is an individual business engaged in the sale of motorcycle accessories and spare parts, located in Pamulang, South Tangerang. The problems experienced by XYZ Motoshop include: difficulty in knowing product availability information, order process is less effective because customers must come directly to the store, sales data processing requires a long time because it is still handwritten, having difficulty to know about shipping goods because it does not have proof of receipt of goods and the customer does not recognize the product being promoted on social media. To solve the above problems, we need a system that is able to manage product sales transactions effectively and efficiently. Researchers offer alternative solutions to help management to solve problems that occur by designing e-commerce systems. In this study, researchers used the Business Model Canvas approach to analyze the company's business model, problem analysis using the Fishbone Diagram approach, analysis and design of the E-Commerce system using the Unified Modeling Language approach and implementation of the E-Commerce system using the Content Management System, the search method using techniques Search Engine Optimization and marketing methods use the 4P marketing strategy. The final results of this research are an E-Commerce Website that can increase sales of motorcycle accessories products in XYZ Motoshop